127k views
6 votes
Solve for X:: show steps please!!

-5(3-x)+4=5x-11

User SkyWriter
by
4.6k points

1 Answer

10 votes

Answer:

Let's solve your equation step-by-step.

−5(3−x)+4=5x−11

Step 1: Simplify both sides of the equation.

−5(3−x)+4=5x−11

(−5)(3)+(−5)(−x)+4=5x+−11(Distribute)

−15+5x+4=5x+−11

(5x)+(−15+4)=5x−11(Combine Like Terms)

5x+−11=5x−11

5x−11=5x−11

Step 2: Subtract 5x from both sides.

5x−11−5x=5x−11−5x

−11=−11

Step 3: Add 11 to both sides.

−11+11=−11+11

0=0

User Prasanna Kumar H A
by
5.6k points